Photo‐Induced Construction and Recovery of Cu + Sites in Metal–Organic Frameworks - Li, Yu‐Xia; Li, Ke‐Di; Qian, Xin‐Yu; Liu, Xiao‐Qin; Sun, Lin‐Bing (Small (Weinheim an der Bergstrasse, Germany), 2023)
The adjustment of the valence state of metal ions is crucial for various applications because peculiar activity originates from metal ions with specific valence. Cu + can interact with molecules possessing unsaturated bonds like CO via π ‐complexation, while Cu 2+ doesn't have such ability. Meanwhile, Cu + sites are easily oxidized to Cu 2+ , leading to the loss of activity. Despite great efforts, the development of a facile method to construct and recover Cu + sites remains a pronounced challenge. Here, for the first time a facile photo‐induced strategy is reported to fabricate Cu + sites in metal–organic frameworks (MOFs) and recover Cu + after oxidation. The Cu 2+ precursor was loaded on NH 2 ‐MIL‐125, a typical visible‐light responsive Ti‐based MOF. Visible light irradiation triggers the formation of Ti 3+ from Ti 4+ in framework, which reduces the supported Cu 2+ in the absence of any additional reducing agent, thus simplifying the process for Cu + generation significantly. Due to π ‐complexation interaction, the presence of Cu + results in remarkably enhanced CO capture capacity (1.16 mmol g −1 ) compared to NH 2 ‐MIL‐125 (0.49 mmol g −1 ). More importantly, Cu + can be recovered conveniently via re‐irradiation when it is oxidized to Cu 2+ , and the oxidation‐recovery process is reversible.